Consumer Protection from Abuses in Commercial Communications sent via Radiofrequency - Jiménez, David López; Dittmar, Eduardo Carlos (Law, State and Telecommunications Review, 2018)
Purpose ”“ The aim of this work is to analyze the commercial communications sent by radiofrequency on the bluetooth network. Methodology/approach/design ”“ An analysis of Spanish and European regulations on commercial communications and data protection. Findings ”“ Industry self-regulation can complement (in several aspects) the regulations applied to this field. Practical implications ”“ The analysis in this article can be of considerable use to all actors who operate in this setting (society, and the public and private sectors). Originality/value ”“ This investigation emphasises the usefulness of self-regulation in the industry (codes of conduct) regarding commercial communications sent by radiofrequency. These instruments constitute an improvement on the regulations, close certain loopholes and can be updated more quickly than the law, and this can enhance user and/or consumer protection.